2010
DOI: 10.1016/j.bbmt.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following Reduced-Intensity Allogeneic Stem Cell Transplantation (RIC AlloSCT) for Relapsed and Refractory Mantle Cell Lymphoma (MCL): A Study of the British Society for Blood and Marrow Transplantation

Abstract: Reduced-intensity allogeneic stem cell transplantation (RIC-AlloSCT) is being increasingly considered for patients with aggressive lymphoma, but limited evidence exists in mantle cell lymphoma (MCL). We report a retrospective study of transplant outcomes of RIC-AlloSCT for MCL in 70 patients (median age, 48 years, range: 30-67 years), with 57 patients receiving an Alemtuzumab-containing regimen. Thirty-four percent of patients had received a prior autologous stem cell transplant. The 1- and 5-year nonrelapse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 32 publications
9
74
0
Order By: Relevance
“…23 Second, will MRD positive patients after intensive induction immunochemotherapy benefit from allogeneic stem cell transplant (Allo-SCT) instead of ASCT at first remission? A recent retrospective study clearly demonstrated that age and the effects of prior therapies predict OS and NRM (non-relapse mortality) after RIC (reduced-intensity conditioning) Allo-SCT in patients with relapsed or refractory MCL, 24 raising the potential value of considering Allo-SCT for the early phase of disease management. Third, could MRD status after intensive induction immunochemotherapy be used to stratify patients for maintenance therapy with either rituximab or another targeted agent, and if sequential monitoring of MRD status could be used to determine the duration of maintenance therapy?…”
Section: Discussionmentioning
confidence: 99%
“…23 Second, will MRD positive patients after intensive induction immunochemotherapy benefit from allogeneic stem cell transplant (Allo-SCT) instead of ASCT at first remission? A recent retrospective study clearly demonstrated that age and the effects of prior therapies predict OS and NRM (non-relapse mortality) after RIC (reduced-intensity conditioning) Allo-SCT in patients with relapsed or refractory MCL, 24 raising the potential value of considering Allo-SCT for the early phase of disease management. Third, could MRD status after intensive induction immunochemotherapy be used to stratify patients for maintenance therapy with either rituximab or another targeted agent, and if sequential monitoring of MRD status could be used to determine the duration of maintenance therapy?…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective single-and multiinstitutional reviews have shown durable PFS of 14% to 46% and OS of 37% to 53%, with evidence of a plateau in the survival curve suggesting cure. [16][17][18] One-year nonrelapse mortality was 18% to 22%. A beneficial effect of donor lymphocyte infusion was documented in some relapsing patients, consistent with a GVL effect.…”
Section: What Is the Role Of Allogeneic Sct?mentioning
confidence: 99%
“…The 3-year-PFS of 57 chemosensitive patients (including 30 patients in first CR/PR) in the British registry Transplantation and beyond in MCL L Chaudhary et al study ranged from 26-31%. 56 Non-randomized registry data from Center for International Blood and Marrow Transplant Research examining the role of allo-HCT vs auto-HCT in MCL patients in first remission (1st CR or PR) showed no benefit in terms of PFS (55% vs 52%) or OS (62% vs 61%), but a significantly higher non-relapse mortality (25% vs 3%) with upfront allografting 57 (Table 4). These data caution against the routine use of allo-HCT for MCL in first remission.…”
Section: Allogeneic Transplantation For MCL In First Remissionmentioning
confidence: 99%